Understanding the impacts of COVID-19 restrictions on smallholder livelihoods and livestock value chains - Galol, A.M.; Baltenweck, Isabelle; Hammond, James (International Livestock Research Institute, 2022)
This synthesis paper compiles the results of CGIAR/ILRI studies related to COVID-19, livestock value chain and livestock- dependent smallholder households. It shows the major trends observed in the studies by researchers, highlights similarities and differences in the locations and value chains, and identifies policies for building better, more resilient and sustainable livestock value chains. A desk review approach was adopted. Both published and unpublished studies (until June 2022) conducted by CGIAR/ ILRI that focus on the impact of the COVID-19 pandemic on livestock value chains and smallholder households were included. The analysis found that the pandemic highlighted key weaknesses in the livestock value chains and some key vulnerabilities of smallholder households and their livelihoods. Throughout the studied locations and value chains, it was evident how the livestock sector and livestock value chains were vulnerable to movement restrictions, supply chain disturbances, and market distortions. The pandemic (and the subsequent movement and other restrictions) impacted negatively businesses, livelihoods, food security and access to essential services for vulnerable smallholder households. This should be an incentive for in-depth re-evaluation to implement evidence-based solutions for building back better, resilient and sustainable livestock value chains, smallholder households’ livelihoods and agri-food systems. Further analysis and studies covering other geographical locations with consideration of a wider range of factors can provide more information on the pandemic’s impact on smallholder farming systems and livestock value chains. These findings alongside those highlighted in this survey will provide evidence-based approaches and solutions for decreasing the vulnerabilities of livestock value chains and increasing smallholder resilience towards more sustainable livelihoods.